Pangan fungsional dari bahan pangan tradisional: tinjauan pustaka - Sia Clarissa Eleora Setiawan; Arri Yuliantara; Paulus Damar Bayu Murti (AGROINTEK, 2024)
With the development of the times, most people often consume fast food or what is commonly referred to as junk food.  The long-term effect causes many people to experience degenerative diseases like heart disease, diabetes, hypertension, cancer, and osteoporosis.  Therefore, there is a need for solutions so that people can maintain a lifestyle to support their health. The solution is in the form of functional food derived from traditional ingredients, such as tempeh, tape, and also several types of spices.  Functional foods are food ingredients that can provide many additional benefits to the body, apart from the basic nutritional functions of these foods.  For example, such as consuming antioxidants derived from phytochemical compounds contained in some of these traditional ingredients.  Phytochemical compounds that can act as antioxidants are used to counteract free radicals that occur in the body.  These antioxidants can be obtained from tempeh, tape, and several spices.  The spices include ginger, kencur, turmeric, temulawak, galangal, and cinnamon. Processed functional food products from several spices are used as health drinks, herbs, teas, juices, syrups, and sweets. Functional food from traditional ingredients has the potential to be developed.  This is due to the sufficient production of raw materials and the community's need for functional food from these traditional ingredients.  Regulations regarding functional food from traditional ingredients are considered insufficient, even though the government has made regulations regarding foods that have special nutrition.  The aim of this study is to elaborate several traditional food ingredients and its function to help in maintaining the health in the body. As a results, this paper presents some research data that has been done previously related to some of the advantages of traditional food ingredients